Influence of fluoride-releasing restorative material on root dentine secondary caries in situ - Hara, A. T.; Turssi, C. P.; Ando, M.; Gonzalez-Cabezas, C.; Zero, D. T.; Rodrigues, A. L.; Serra, Mônica da Costa [UNESP]; Cury, J. A. (Karger, 2006)
The usefulness of fluoride-releasing restorations in secondary caries prevention may be questioned because of the presence of other common sources of fluoride and because of ageing of the restorations. This study tested the hypothesis that glass-ionomer cement restorations, either aged or unaged, do not prevent secondary root caries, when fluoride dentifrice is frequently used. Sixteen volunteers wore palatal appliances in two phases of 14 days, according to a 2 x 2 crossover design. In each phase the appliance was loaded with bovine root dentine slabs restored with either glass-ionomer or resin composite, either aged or unaged. Specimens were exposed to cariogenic challenge 4 times/day and to fluoridated dentifrice 3 times/day. The fluoride content in the biofilm (FB) formed on slabs and the mineral loss (Delta Z) around the restorations were analysed. No differences were found between restorative materials regarding the FB and the Delta Z, for either aged (p = 0.792 and p = 0.645, respectively) or unaged (p = 1.00 and p = 0.278, respectively) groups. Under the cariogenic and fluoride dentifrice exposure conditions of this study, the glass-ionomer restoration, either aged or unaged, did not provide additional protection against secondary root caries. Copyright (c) 2006 S. Karger AG, Basel.
Keywords: glass-ionomer cement; root caries; secondary caries